Pengujian Kekuatan Retak Komposit Arang Tempurung yang Dihaluskan Sebagai Bahan Baku Penganti Kayu untuk Kapal Nelayan - Nusyirwan, Nusyirwan; Rani, Mutya (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
Coconut shell charcoal is a by-product waste from coconut farming which is very abundant and its use has not been optimally applied other than being limited to burning it for boiler energy as a heater and other parts of it being used as a fuel source for cooking. As raw materials for making wooden boats for fishermen in Indonesia become increasingly scarce, efforts are needed to find replacement materials in the supply process. However, another very urgent factor is that it is absolutely necessary to develop environmentally friendly composites to replace synthetic composites which are difficult to decompose. However, composite materials made from natural fibers still have many weaknesses, including low mechanical strength, therefore applications in the engineering field are still under study and development. Some of the weaknesses of natural fiber composite materials, which need to be studied, include their brittle nature and easy cracking. One of the things carried out in this research is a synthetic material derived from unsaturated polyester reinforced with natural fibers from coconut shell charcoal particles which is used to reduce the percentage of synthetic material from polyester which can form a composite that is easily decomposed. From the research, the mechanical strength obtained with a polyester mixture matrix reinforced with coconut shell charcoal fibers obtained crack resistance values with a large critical stress intensity factor based on ASTM D 5405 by varying the composition of the shell charcoal fiber mixture from: 0%, 10%, 20%, to 30%. From the test results, the largest critical stress intensity factor at K_1c= 1.624 (MPa/m1/2) occurred in 20% coconut shell charcoal fiber.